Midwifery Care for Neonates with Jaundice - Deva Salvana Andrianingsih; Desy Dwi Cahyani; Finta isti kundarti (KHD Production, 2025)
Excess bilirubin accumulation occurs in 60% of babies born on time and 80% of premature babies in the first week of life, causing the skin and sclera to turn yellow. This condition is called neonatal jaundice. It is important to provide appropriate treatment so that severe complications such as kernicterus and permanent neurological damage can be avoided. This study aims to analyze Midwifery Care for Neonates with Jaundice. This study applied a case study design with a comprehensive approach to midwifery care in one patient. Information was collected through interviews, observations, physical examinations, and documentation studies. The data was then analyzed by following the stages of the midwifery process, which include assessment, diagnosis, intervention, implementation, and evaluation. A case study was conducted on baby A, aged 7 days with a birth weight of 3020 grams, who had jaundice on the face, neck, and chest. The diagnosis was a 7-day-old full-term neonate with physiological jaundice. The intervention was conducted by educating mothers to dry the baby for 10-15 minutes before 10 am and breastfeed as often as possible, 8-12 times a day. Evaluation at the second visit showed that the facial, neck, and chest jaundice was no longer visible, and the body weight increased from 3010 grams to 3030 grams. This case demonstrates the effectiveness of non-pharmacological interventions in managing physiological jaundice. An educative approach through adequate breastfeeding and exposure to morning sunlight as natural phototherapy is proven to be safe and easy to do at home.